Effect of surfactants on drop formation flow patterns in a flow-focusing microchannel. (18th May 2022) - Kalli, Maria; Angeli, Panagiota
Highlights: Drop formation flow patterns at surfactant concentrations below and above CMC. Effect of surfactant type and concentration on the boundaries of dripping and jetting patterns. Effect of surfactant activity on drop formation time. Measured dynamic interfacial tension in the millisecond scale for dripping and jetting patterns. Dripping and jetting flow pattern boundaries collapse with dynamic interfacial tension. Abstract: The formation of droplets in an immiscible liquid in the presence of different surfactants was studied experimentally using a flow-focusing microchannel. A low viscosity silicone oil (4.6 mPa s) was used as the continuous phase and a mixture of 48% w/w water and 52% w/w glycerol was the dispersed phase. A cationic (CMCDTAB  = 20 mM), an anionic (CMCSDS  = 11 mM), and a non-ionic (CMCTX100  = 3.5 mM) surfactant were added in the aqueous phase, at several concentrations. Five patterns of drop formation were identified, namely squeezing, dripping, jetting, threading and tip streaming/jetting, whose boundaries were affected by the surfactant type and concentration. Using dynamic interfacial tension values, it was possible to plot a universal flow pattern map with the capillary numbers of the two phases as coordinates, where the transition boundaries between the dripping and the jetting patterns collapsed for all fluid systems considered, including the solutions with and without surfactants.